2022
DOI: 10.1038/s41598-022-08519-z
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of hypoxia in the affected tissue of relapsed clubfoot

Abstract: Our aim was to study the expression of hypoxia-related proteins as a possible regulatory pathway in the contracted side tissue of relapsed clubfoot. We compared the expression of hypoxia-related proteins in the tissue of the contracted (medial) side of relapsed clubfoot, and in the tissue of the non-contracted (lateral) side of relapsed clubfoot. Tissue samples from ten patients were analyzed by immunohistochemistry and image analysis, Real-time PCR and Mass Spectrometry to evaluate the differences in protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(71 reference statements)
1
4
0
Order By: Relevance
“…The increased HIF1A gene in response to ongoing hypoxia would stimulate the production of TGFb1 as a cytokine which led to myofibroblast trans-differentiation, reflected in the raised expression of ACTA2 gene expression and its protein, SmActin. 2 Similar to the previous study result discussed by Ošťádal et al, these samples' collagen type III and VI levels on the medial clubfoot side were also increased compared to its lateral side. 17 These changes in extracellular matrix protein expression, along with their corresponding genes from these feet samples, shed light on the role of hypoxia-induced fibrotic changes within recurrent ICTEV cases.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…The increased HIF1A gene in response to ongoing hypoxia would stimulate the production of TGFb1 as a cytokine which led to myofibroblast trans-differentiation, reflected in the raised expression of ACTA2 gene expression and its protein, SmActin. 2 Similar to the previous study result discussed by Ošťádal et al, these samples' collagen type III and VI levels on the medial clubfoot side were also increased compared to its lateral side. 17 These changes in extracellular matrix protein expression, along with their corresponding genes from these feet samples, shed light on the role of hypoxia-induced fibrotic changes within recurrent ICTEV cases.…”
supporting
confidence: 89%
“…Socioeconomic factors and familial and treatment compliance have illustrated their effects in causing relapses in some patients. 2,[9][10][11] Unfortunately, the role of genes, which had been in question for a while, has shown to be understudied, as seen by the insufficient number of studies. Genetic causes have been linked to the occurrence of idiopathic clubfoot after studies showed linkage through positive family history, twin studies, higher incidence in certain areas and gender.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxic induction of COL1 deposition has been known for 40 years and confirmed in several studies ( 142 145 ). Other studies also show HIF-mediated deposition and/or gene expression of fibrillar COLs (COL3 ( 146 ), COL5 ( 147 150 ), COL11 ( 149 , 151 ) and COL27 ( 149 )), basement membrane COLs (COL4 ( 150 , 152 , 153 ), COL7 ( 154 ), COL10 ( 151 , 155 ) and COL18 ( 153 , 156 )), filament-forming COLs (COL6 ( 146 )), fibril-associated COLs (COL9 ( 150 , 151 ), COL14 ( 157 )) and transmembrane COLs (COL13 ( 150 )). Recent studies show hypoxia can also enhance fibrosis through increasing FN expression ( 158 , 159 ).…”
Section: Hypoxia and The Extracellular Matrix In Cancermentioning
confidence: 93%